Specific Features of the African Early State - Claessen, Henri J.M. (L’Uomo Società tradizione sviluppo, 2019)
This article investigates whether African early states (south of the Sahara) show organizational features that can be labeled typically, or specifically African. To reach this goal first the concept of the early state is presented. Then the problem of “specific features” is dealt with. It is suggested that specific features are found mainly in those parts of the structure, in which a certain degree of variation is possible, without affecting the more general structure of the early state. These include variation in the aspects of sacrality, variation in the mode of succession, variation in the position of royal women etc. Ethnographic data on eight African early states (Ankole, Rwanda, Buganda, Yoruba, Dahomey, Kuba, Tio, and Swazi) are presented and compared in order to find common features. The African data are compared in each case with the findings in a control group made up of the Polynesian early states Tahiti and Tonga, and the realm of the Incas. In the end a number of specific African features are suggested — with the possibility that the data are valid only for peoples reached by the so-called Bantu expansion. Il presente articolo si propone di prendere in esame le forme arcaiche di stato africano, localizzate a sud del Sahara, per comprendere se le caratteristiche organizzative possano essere considerate tipicamente o specificamente africane. A tale scopo viene innanzitutto presentato il concetto di stato arcaico, cui segue la trattazione del problema delle “caratteristiche specifiche”. L'A. ritiene che queste ultime siano individuabili essenzialmente in quelle parti della struttura in cui è possibile un certo grado di variabilita, senza che sia intaccata la struttura generale dello stato arcaico. Si possono dunque avere variazioni negli aspetti della sacralità, nel modo della successione, nella posizione delle donne di sangue reale ecc. I dati etnografici relativi a otto stati arcaici africani (Ankole, Rwanda, Buganda, Yoruba, Dahomey, Kuba, Tio, Swazi), vengono esaminati e paragonati per documentarne le caratteristiche comuni; in ciascun caso inoltre i dati africani vengono comparati con quelli di un gruppo di controllo costituito dagli stati arcaici polinesiani di Tahiti e Tonga e dal regno degli Inca. Nella conclusione l’A. riporta alcune caratteristiche specificamente africane, suggerendo la possibilita che i dati siano validi solo per le popolazioni raggiunte dalla cosiddetta espansione bantu.